ESSAY ON THE FIRST ANNIVERSARY IN MEMORY OF THE OUTSTANDING DOCTOR, SCIENTIST AND TEACHER LEV VLADIMIROVICH SYTIN - Жестикова, Марина Григорьевна (Medicine in Kuzbass, 2022)
Sytin Lev Vladimirovich – candidate of medical sciences, traumatologist-orthopedist, scientist, teacher, first general director of the Novokuznetsk Scientific and Practical Center for Medical and Social Expertise and Rehabilitation of the Disabled, taught at the department of rehabilitation at the Novokuznetsk State Institute for Postgraduate Medical Education.